How to Teach Science to Toddlers? - Nabila, Siti Maulidiya; Al-Qoyyim, Thufail Mujaddid (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
Science education for toddlers is crucial in building early scientific understanding and fostering curiosity. However, several challenges persist in its implementation, such as teaching methods that are not well-suited to early childhood characteristics, limited exploratory facilities, and a lack of understanding among parents and educators regarding effective teaching strategies. This study analyzes various approaches that can be used to teach science to toddlers effectively and engagingly. The methods discussed include inquiry-based learning, hands-on activities, sensory exploration, construction play, and nature observation. Additionally, connecting science with daily life is an essential strategy to help children understand the relevance of scientific knowledge in the real world. The analysis results indicate that exploration-based and hands-on learning approaches enhance children's understanding of scientific concepts more effectively than traditional instructional methods. The active role of parents and educators in guiding children, providing reflective questions, and creating a supportive learning environment significantly influences learning success. With the right strategies, children grasp scientific concepts and develop critical thinking skills, problem-solving abilities, and an early love for science.